2023
DOI: 10.1108/ijis-08-2022-0136
|View full text |Cite
|
Sign up to set email alerts
|

Examine the level of environmental, social and governance disclosure in sustainability report – a study of the Indian banking sector

Abstract: Purpose Sustainable development (SD) is widely acknowledged as the center around which all development efforts should revolve. Banking is a crucial component of SD, and the adoption of sustainable banking practices by various banking institutions is a powerful catalyst for its achievement. This paper aims to investigate the level of adoption of environmental, social and governance (ESG) indicators in India and the extent to which financial institutions use these strategies. In addition, the banks have been cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Companies must shift their focus from optimizing profits to increasing shareholder value to value creation for stakeholders [7]. Companies can take action to meet these expectations and pressures by carrying out operational activities that can meet current needs without sacrificing the future capabilities of the next generation [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Companies must shift their focus from optimizing profits to increasing shareholder value to value creation for stakeholders [7]. Companies can take action to meet these expectations and pressures by carrying out operational activities that can meet current needs without sacrificing the future capabilities of the next generation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Companies can take action to meet these expectations and pressures by carrying out operational activities that can meet current needs without sacrificing the future capabilities of the next generation [8,9]. In its implementation, companies must include environmental, social, and governance factors to assess their sustainability performance [7,10]. However [11] revealed that more than the company's efforts to fulfill these expectations are needed through actions and communicating them.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the banking sector, as a financial institution, is consistently required to develop standards and practices by integrating sustainability criteria into their business strategies under the comprehensive global development framework (Kashi and Shah, 2023). Currently, the demand for sustainable business practices is rapidly increasing, and implementing sustainable banking strategies can become a competitive advantage to enhance customer loyalty (Mishra and Sant, 2023). However, approximately 60% of banks have not effectively implemented climate risk stress testing, and most financial institutions are still in the early stages of climate risk framework development (European Central Bank, 2022).…”
mentioning
confidence: 99%